DEVELOPMENT OF FROVATRIPTAN SUCCINATE MICROEMULSION FOR NASAL DELIVERY: OPTIMIZATION, IN VITRO AND IN VIVO EVALUATION - UPENDRA C GALGATTE; PRAVIN D CHAUDHARI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of the present research work was to develop, optimize, and characterize microemulsion (ME) of frovatriptan succinate to improve brain transport. Methods: The pseudoternary phase diagrams were constructed for ME formulations composed of Capmul MCM, Cremophor EL, and propylene glycol. Frovatriptan succinate-loaded ME was optimized by simplex lattice design having the concentration of oil, surfactant, and cosurfactant representing three apex points on the triangle. These were taken as independent variables and percentage drug release as a response variable. All developed batches of ME were characterized for in vitro tests, histopathology study, and pharmacokinetics in Swiss albino rats. Results: Clear MEs were obtained. F5 having particle size – 142.0 nm, zeta potential – 17.7–−7.8 mv, refractive index – 1.38±0.20, drug content – 98.24±0.20%, and drug diffused through dialysis membrane – 85% was the optimized batch. Drug permeation through the nasal mucosa of F5 in the ex vivo study was found to be 82.32%. Histopathology microscopic study has shown that F5 does not cause any irritation and structural changes in sheep nasal mucosa. The pharmacokinetic parameters were determined after nasal and oral administration of F5. For brain tissue, after nasal administration were Cmax181±1.51 ng/ml, Tmax – 2±1.01, area under curve (AUC)0−6 – 390.0±2.08 ng.h/ml. The AUC0−6 attained by nasal ME was 3.29 times greater than oral solution. Drug targeting index of frovatriptan succinate was 2.06. This was found satisfactory. Conclusion: Microemulsion of said composition was found to be enhancing delivery of frovatriptan succinate to brain tissues through nasal route.